A cast complex phase steel material suitable for semi-autogenous mill lining and its preparation method
By introducing martensite structure and reducing the austenite content into the SAG grinder lining material, and using the isothermal quenching process to prepare cast multi-phase steel materials, the problems of short service life and insufficient wear resistance of the SAG grinder liner are solved. , achieving high wear resistance and cracking resistance of the material.
Patent Information
- Application Number
- CN202310426187.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-04-20
AI Technical Summary
The existing semi-self-grinder lining materials have problems such as short life, fracture and insufficient wear resistance in applications, resulting in limited production efficiency and economic benefits of mine ore dressing.
A cast multi-phase steel material is used, which includes 45% to 55% martensite structure, 40% to 45% bainite structure and 5% to 10% residual austenite structure. It is prepared through an isothermal quenching process to reduce the austenite in the material. The content of the body reduces tissue transformation and tissue transformation stress.
The wear resistance and cracking resistance of the material are significantly improved, the service life of the SAG grinder lining is extended, the cracking problem is solved, and the yield rate and the stability of the production process are improved.
Smart Images

Figure CN116426827B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cast steel materials, and in particular to a cast complex phase steel material suitable for a semi-autogenous mill liner and a preparation method thereof. Background Art
[0002] With the development of large-scale mines at home and abroad, mining equipment is required to be large-scale, energy-efficient, green and high-operating. As the core equipment of the mining beneficiation process, the performance of large-scale semi-autogenous mills and ball mills directly affects the efficiency of the beneficiation production line and the economic benefits of the mine; in particular, the service life of the lining of large mill consumable parts is a key factor affecting efficiency and benefits. Famous suppliers at home and abroad are constantly conducting research on improving the service life of the lining, but the traditional CrMo steel casting lining has reached the ceiling and it is difficult to make new breakthroughs. In recent years, steel-rubber composite linings have been used on large mills. Most of the composite linings of large semi-autogenous mills use wear-resistant steel plates, and their service life has not been greatly improved. In order to make a major breakthrough in improving service life, it is necessary to seek alloy materials with impact resistance, high hardness and wear resistance.
[0003] At present, alloy steel for mining machinery is large in size and specifications, and its composition, organization control, and defects have become the key to restricting the application of this type of wear-resistant steel. At present, the alloy steel lining process used in China is mainly medium-frequency furnace smelting, sand casting, and direct casting to form the required lining. The surface quality is slightly rough, and the core hardness of the thick and large section is low. At the same time, due to the existence of component segregation, coarse grains, more slag inclusions, and casting defects, the product will crack or have insufficient wear resistance during application.
[0004] The working condition of the SAG mill liner is very poor. It not only protects the cylinder of the SAG mill, but also has to withstand repeated impacts from grinding balls and ore, which can easily cause the SAG mill liner to fail. In actual applications, there are three forms of failure: fracture, wear, and deformation, among which liner fracture is the main form of failure. There are many reasons for liner fracture failure and it is relatively complicated to study, including external factors and internal factors. Among them, external factors include the low toughness and strength of the liner itself, the harsh environment, etc.; internal factors include defects caused by the liner during smelting, shrinkage or shrinkage, inclusions or unreasonable heat treatment process, etc., which will affect the use of the liner.
[0005] At present, the commonly used SAG mill lining materials are generally 60CrMo, 70CrMo, 85CrMo and Hardox rubber composite, etc., which have problems such as short life, breakage and out of sync with the end lining and grating during application. The lack of wear resistance and short life of these materials are the main reasons that restrict mining customers from improving mineral processing efficiency.
[0006] The cast bainite steel material disclosed in the prior art was found to still have a small amount of cracking problems under particularly harsh conditions in industrial and mining through installation trials; by analyzing the causes of the cracking, it was found that it was mainly due to the presence of 20-30% of residual austenite in the cast bainite steel material, which undergoes structural transformation under greater impact conditions, that is, the residual austenite transforms into martensite, thereby generating greater structural transformation stress and causing cracking. Therefore, reducing the austenite in the steel material and reducing the structural transformation may reduce the cracking of the steel material in use. Summary of the invention
[0007] The object of the present invention is to provide a cast complex phase steel material suitable for semi-autogenous mill linings and a preparation method thereof, by introducing martensite structure into the matrix structure and reducing the content of bainite and residual austenite in the material, so as to achieve the technical effect of reducing the structural transformation of the semi-autogenous mill lining made of steel material during application, avoiding the generation of structural transformation stress and reducing cracking.
[0008] To achieve the above-mentioned object, the present invention proposes the following technical scheme: a cast complex phase steel material suitable for use in a semi-autogenous mill liner, comprising the following chemical components in mass percentage: C is 0.2-0.4wt%, Si is 1.0-1.5wt%, Mn is 1.5-2.5wt%, Cr is 0.5-1.0wt%, Mo is 0.2-0.5wt%, Cu is 0.2-0.5wt%, Ni is 0.2-0.5wt%, Al is 0.02-0.06wt%, P is ≤0.03%, S is ≤0.025%, and the rest is Fe and unavoidable impurities.
[0009] Furthermore, the organizational structure of the cast complex phase steel material includes 45-55% of martensite structure, 40-45% of bainite structure, and 5-10% of retained austenite structure.
[0010] Furthermore, the hardness of the cast complex phase steel material is 45-50HRC.
[0011] Furthermore, the U-notch impact toughness of the cast complex phase steel material is not less than 30 J / cm 2 .
[0012] Furthermore, the cast complex phase steel material includes the following chemical components in mass percentage: C is 0.3-0.4wt%, Si is 1.3-1.5wt%, Mn is 1.5-2.0wt%, Cr is 0.6-0.9wt%, Mo is 0.3-0.4wt%, Cu is 0.3-0.4wt%, Ni is 0.4-0.5wt%, Al is 0.03-0.06wt%, P is ≤0.03%, S is ≤0.025%, and the rest is Fe and unavoidable impurities.
[0013] Another technical solution of the present invention is to disclose a method for preparing a cast complex phase steel material suitable for a semi-autogenous mill liner, comprising the following steps:
[0014] 1) Smelting in a medium frequency electric furnace to obtain molten iron having the following chemical composition by weight percentage: C is 0.2-0.4wt%, Si is 1.0-1.5wt%, Mn is 1.5-2.5wt%, Cr is 0.5-1.0wt%, Mo is 0.2-0.5wt%, Cu is 0.2-0.5wt%, Ni is 0.2-0.5wt%, Al is 0.02-0.06wt%, P is ≤0.03%, S is ≤0.025%, and the rest is Fe and unavoidable impurities;
[0015] 2) The smelting temperature is raised to 1600℃~1650℃, and the molten iron is poured out of the furnace, and the pouring temperature of the molten iron is controlled to be 1500℃~1550℃;
[0016] 3) adopting resin sand molding process, the molding sand is jelly sand, and furan resin and benzenesulfonic acid curing agent are added; wherein the mass ratio of jelly sand to sand iron of casting is 3-5:1, the amount of furan resin added is 1.1-1.2% of the mass of jelly sand, and the amount of benzenesulfonic acid curing agent added is 30-50% of the mass of furan resin;
[0017] 4) The castings that have been unpacked, cooled to room temperature and then cleaned are pretreated in a heat treatment furnace, wherein the pretreatment includes two processes of normalizing and isothermal spheroidizing annealing performed in sequence; wherein the normalizing process is to keep the castings in a furnace at 950-1050° C. for 4-8 hours, and then air-cool them to room temperature after being taken out of the furnace; and the isothermal spheroidizing annealing process is to keep the castings in a furnace at 800-900° C. for 4-8 hours, and then cool them to 700-750° C. for 4-8 hours with the furnace, and then air-cool them to room temperature;
[0018] 5) The pretreated casting is subjected to isothermal quenching treatment, wherein the casting is heated to 900-950° C. in a heat treatment furnace and kept at this temperature for 4-8 hours, then quickly transferred to a salt bath for isothermal quenching, and then kept at 230-250° C. for 4-6 hours before being taken out of the furnace;
[0019] 6) The casting after isothermal quenching treatment is tempered twice to obtain a cast complex phase steel material, wherein the temperature of the first tempering treatment is 300-350° C., the temperature of the second tempering treatment is 200-250° C., and the holding time is 4-8 hours respectively.
[0020] Furthermore, the raw materials for obtaining molten iron by smelting in a medium frequency electric furnace in step 1) include scrap steel, carburizer, low carbon ferrochrome, ferromolybdenum, nickel plate, copper plate, ferromanganese, ferrosilicon, and aluminum wire added sequentially into the medium frequency electric furnace.
[0021] Furthermore, when the casting is pretreated or isothermal quenched in a heat treatment furnace, when the temperature in the heat treatment furnace is less than 650°C, the temperature is increased at a rate of 100-150°C / h; when the temperature in the heat treatment furnace exceeds 650°C, the temperature is increased at a rate of 150-200°C / h.
[0022] Furthermore, in step 4), the casting is cooled in the sand box to below 400° C., and then the sand box is opened.
[0023] The invention also discloses the application of the above-mentioned cast complex phase steel material suitable for semi-autogenous mill lining plate on the semi-autogenous mill lining plate.
[0024] It can be seen from the above technical solutions that the technical solutions of the present invention have the following beneficial effects:
[0025] The present invention discloses a cast complex phase steel material suitable for a semi-autogenous mill liner and a preparation method thereof, wherein the steel material comprises the following chemical components in mass percentage: C 0.2-0.4wt%, Si 1.0-1.5wt%, Mn 1.5-2.5wt%, Cr 0.5-1.0wt%, Mo 0.2-0.5wt%, Cu 0.2-0.5wt%, Ni 0.2~0.5wt%, Al0.02~0.06wt%, P≤0.03%, S≤0.025%, and the rest are Fe and inevitable impurities; the preparation method adopts isothermal quenching process to obtain martensite, bainite and residual austenite matrix structures with excellent comprehensive performance, specifically including 45~55% martensite structure, 40~45% bainite structure, and 5~10% austenite structure, and by introducing about 50% martensite structure into the matrix structure, the content of residual austenite in the material is effectively reduced, and then when the semi-autogenous mill liner undergoes a small amount of or no organizational transformation under a large impact condition, the organizational transformation stress generated is greatly reduced, and the liner failure caused by cracking is reduced.
[0026] Compared with bainitic steel, 60CrMo, 70CrMo, 85CrMo and Hardox plate rubber composite materials, the cast complex phase steel material prepared by the present invention can effectively improve the wear resistance and cracking resistance of the material. The addition of Mo, Ni, Cu and Cr significantly improves the hardenability of the material. The isothermal quenching process effectively strengthens the matrix structure and ensures the mechanical properties of the steel material. While meeting the high wear resistance, the present invention effectively improves the toughness of the material itself. The prepared semi-autogenous mill liner has high wear resistance, high yield and stable production process, and completely solves the cracking problem of the semi-autogenous mill liner.
[0027] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, may be considered to be part of the inventive subject matter of the present disclosure, provided such concepts are not mutually inconsistent.
[0028] The foregoing and other aspects, embodiments and features of the present invention can be more fully understood from the following description in conjunction with the accompanying drawings. Other additional aspects of the present invention, such as the features and / or beneficial effects of the exemplary embodiments, will be apparent from the following description or learned from the practice of the specific embodiments according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings are not intended to be drawn to scale. In the drawings, each identical or nearly identical component shown in various figures may be represented by the same reference numeral. For clarity, not every component is labeled in every figure. Embodiments of various aspects of the present invention will now be described by way of example and with reference to the accompanying drawings, in which:
[0030] Figure 1 This is the metallographic (200X) organization diagram of the cast complex phase steel material obtained in Example 1;
[0031] Figure 2 This is the metallographic (500X) organization diagram of the cast complex phase steel material obtained in Example 1;
[0032] Figure 3 This is an example diagram of the application of a liner made of the cast complex phase steel material obtained in Example 1. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme of the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0034] The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, unless the context clearly indicates otherwise, the singular forms of "a", "an" or "the" and other similar words do not indicate a quantitative limitation, but indicate the existence of at least one. Words such as "include" or "comprise" mean that the elements or objects appearing before "include" or "comprise" cover the features, wholes, steps, operations, elements and / or components listed after "include" or "comprise", and do not exclude the existence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.
[0035] Based on the existing technology, the SAG mill linings made of cast bainitic steel, 60CrMo, 70CrMo, 85CrMo and Hardox plate rubber composite materials have the problems of short service life, fracture and asynchronism with end linings and grating plates during application; the present invention aims to completely solve the cracking problem of SAG mill linings, proposes a cast complex phase steel material suitable for SAG mill linings and a preparation method thereof, utilizes advanced isothermal quenching technology to obtain martensite, bainite and residual austenite matrix structures with excellent comprehensive performance, and makes the SAG mill linings have high wear resistance, high yield rate and stable production process.
[0036] Specifically, the preparation method of the cast complex phase steel material suitable for semi-autogenous mill lining disclosed in the present invention comprises the following steps: 1) smelting in a medium frequency electric furnace to obtain molten iron with the following chemical composition by weight percentage: C is 0.2-0.4wt%, Si is 1.0-1.5wt%, Mn is 1.5-2.5wt%, Cr is 0.5-1.0wt%, Mo is 0.2-0.5wt%, Cu is 0.2-0.5wt%, Ni is 0.2-0.5wt%, Al is 0.02-0.06wt%, P is ≤0.03%, S is ≤0.025%, and the rest is Fe and unavoidable impurities; 2) the smelting temperature is raised to 1600°C-1650°C, the molten iron is poured out of the furnace, and the pouring temperature of the molten iron is controlled to be 1500°C-1550°C; 3) a resin sand molding process is adopted, the molding sand is gem sand, furan resin and benzenesulfonic acid curing agent are added; wherein, The mass ratio of the pearl sand to the iron sand of the casting is 3 to 5:1, the amount of the furan resin added is 1.1 to 1.2% of the mass of the pearl sand, and the amount of the benzenesulfonic acid curing agent added is 30 to 50% of the mass of the furan resin; 4) the castings that have been unpacked, cooled to room temperature and cleaned are pretreated in a heat treatment furnace, and the pretreatment includes two processes of normalizing and isothermal spheroidizing annealing performed in sequence; wherein the normalizing process is to heat the casting in the furnace at 950 to 10 The casting is kept at 50℃ for 4-8h, and then air-cooled to room temperature. The isothermal spheroidizing annealing process is that the casting is kept at 800-900℃ in the furnace for 4-8h, cooled to 700-750℃ with the furnace and kept at 4-8h, and then air-cooled to room temperature; 5) The casting after pretreatment is subjected to isothermal quenching treatment. The process of isothermal quenching treatment is that the casting is heated to 900-950℃ in the heat treatment furnace and kept at 4-8h, and then quickly transferred to the salt tank for isothermal quenching, 230-25
[0037] 0℃ for 4-6h, then take out of the furnace, cool to ≤80℃ after taking out of the furnace, and then clean and temper; 6) the casting after isothermal quenching is tempered twice to obtain the casting complex phase steel material, wherein the temperature of the first tempering treatment is 300-350℃, the temperature of the second tempering treatment is 200-250℃, and the insulation time is 4-8h respectively; wherein, when the casting is pretreated or isothermal quenched in the heat treatment furnace, when the temperature in the heat treatment furnace is less than 650℃, the temperature is increased at a rate of 100-150℃ / h; when the temperature in the heat treatment furnace exceeds 650℃, the temperature is increased at a rate of 150-200℃ / h. Through the above method, the casting complex phase steel material suitable for semi-autogenous mill lining can be stably produced.
[0038] The structure of the cast complex phase steel material includes 45-55% martensite, 40-45% bainite and 5-10% austenite, and the material hardness is 45-50HRC and the U-notch impact toughness is not less than 30J / cm 2 .
[0039] Controlling the chemical composition and mass percentage of the cast complex phase steel material can improve the mechanical properties of the steel material. The design basis of the effective chemical composition of the cast complex phase steel material of the present invention and the reasons for limiting the content range are as follows:
[0040] C is one of the main elements in steel, belonging to interstitial solid solution strengthening, and is the main element that can stabilize the retained austenite; the amount of C added will seriously affect the strength, hardness and plasticity. According to the environment and working conditions of the complex phase steel liner, the amount of C added is controlled at 0.2-0.4wt%;
[0041] Si can cooperate with alloy elements such as Cr, Mn, and C in steel to increase the hardenability of steel during isothermal quenching and hinder the formation of carbides. As the Si content increases, the solid solution of carbon in austenite decreases, thereby promoting the diffusion of C. Excessive Si reduces the toughness of the material and makes it easy to quench cracks. In addition, the content of residual austenite increases, the hardness of the steel decreases, and the toughness and strength decrease, and the tough-brittle transition temperature increases. Therefore, the amount of Si added is controlled at 1.0-1.5wt%;
[0042] Mn can significantly improve the hardenability of steel. The Ms point decreases with the decrease of Mn content, and the Bs point increases with the increase of Mn content. Mn can be used as a desulfurizer and deoxidizer. The increase of Mn content increases the stability of retained austenite, so the addition amount of Mn is controlled to 1.5-2.5wt%;
[0043] Cr has a significant effect on the deformation resistance of steel materials after quenching, and can improve the mechanical properties of steel such as hardness and wear resistance; Cr can slow down the rate of decomposition and transformation of supercooled austenite, thereby improving the hardenability of steel, and can play a role in solid solution strengthening; the Cr content in low alloy steel is generally less than 2%, and the temper brittleness of steel will increase when the Cr content exceeds a certain amount; therefore, the addition amount of Cr in the scheme is controlled to 0.5-1.0wt%;
[0044] Mo can significantly reduce the critical cooling rate of steel and has the strongest effect on the hardenability of steel. Mo dissolved in steel has a strong ability to prevent the growth of austenite grains when heated and can significantly increase the recrystallization temperature of steel. Therefore, the amount of Mo added is controlled to 0.2-0.5wt%.
[0045] Ni and Cu are non-carbide forming elements. When they exist in steel in the form of solid solution and are used in combination with Cr, a small amount of Ni and Cu can significantly improve the hardenability and strength of the steel, and at the same time have the effect of refining the grains, which is beneficial to improving the toughness of the steel material. In the scheme, the addition amounts of Ni and Cu are controlled at 0.2-0.5wt% respectively.
[0046] S and P are harmful substances in the material, the less the better, but they are inevitably brought into the molten iron in the raw materials, so from the perspective of material performance and cost, the content of S and P is limited.
[0047] The following is a further detailed introduction to the cast complex phase steel material suitable for SAG mill liner and the preparation method thereof disclosed in the present invention in conjunction with specific embodiments.
[0048] Example 1
[0049] 92.5% scrap steel, 0.03% carburizer, 1.45% low-carbon ferrochrome, 0.7% ferromolybdenum, 0.48% nickel plate, 0.4% copper plate, 2.75% ferromanganese, 1.7% ferrosilicon and 0.03% aluminum wire are sequentially added into a medium frequency electric furnace to obtain molten iron with the composition of casting complex phase steel materials, specifically including: 1850 kg scrap steel, 0.55 kg carburizer, 29.5 kg low-carbon ferrochrome, 13.5 kg ferromolybdenum, 9.5 kg nickel plate, 8 kg copper plate, 54.5 kg ferromanganese, 33.9 kg ferrosilicon and 0.55 kg aluminum wire, which are sequentially added into a 2-ton medium frequency furnace for heating and melting. When the molten iron reaches 1600°C, samples are taken for analysis and the composition is adjusted according to the test results. After the composition is qualified, the temperature is increased and deoxidized, and the molten iron is taken out of the furnace at 1640°C. When the temperature in the ladle reaches 1550°C, the casting is poured.
[0050] Example 2
[0051] The difference between Example 2 and Example 1 is that 1480 kg of scrap steel, 397 kg of recycled materials of Example 1, 0.36 kg of recarburizer, 24.5 kg of low-carbon ferrochrome, 10.5 kg of ferromolybdenum, 7.5 kg of nickel plate, 6.5 kg of copper plate, 46 kg of ferromanganese, 27.5 kg of ferrosilicon and 0.14 kg of aluminum wire are sequentially added into a 2-ton medium frequency furnace for heating and melting, and the molten iron is sampled and analyzed when it reaches 1580°C, and the composition is adjusted according to the test results; after the composition is qualified, the temperature is raised and deoxidized, and the casting is taken out of the furnace at 1630°C; when the temperature in the ladle reaches 1530°C, the casting is poured;
[0052] Example 3
[0053] The difference between Example 3 and Example 1 is that 1290 kg of scrap steel, 605 kg of recycled materials of Example 2, 0.28 kg of recarburizer, 22.5 kg of low-carbon ferrochrome, 9.5 kg of ferromolybdenum, 6.5 kg of nickel plate, 5.5 kg of copper plate, 35.78 kg of ferromanganese, 24.5 kg of ferrosilicon, and 0.44 kg of aluminum wire are sequentially added into a 2-ton medium frequency furnace for heating and melting. When the molten iron reaches 1610°C, sampling and analysis are performed, and the composition is adjusted according to the test results; after the composition is qualified, the temperature is raised and deoxidized, and the casting is taken out of the furnace at 1620°C; when the temperature in the bag reaches 1510°C, the casting is poured.
[0054] The castings of Examples 1 to 3 are cooled to below 400° C. in a sand box, generally 40 hours after pouring, unpacked, and after cooling to room temperature, the pouring and riser are removed, and then polished; the polished castings are sequentially pretreated, isothermal quenched and tempered in a heat treatment furnace to obtain a cast complex phase steel liner suitable for semi-autogenous mill liner; specifically, the process parameters for pretreatment, isothermal quenching and tempering of Examples 1-3 are shown in Table 1 below.
[0055] Table 1 Heat treatment process parameters of Examples 1-3
[0056]
[0057] During the treatment, the temperature fluctuation range of each process is as defined in the above method steps. The chemical composition and hardness value of the cast complex phase steel material suitable for semi-autogenous mill liner prepared in Examples 1-3 are shown in Table 2 below.
[0058] Table 2 Proportions of other chemical components in Examples 1-3 except Fe and unavoidable impurities
[0059]
[0060] The metallographic structure of the cast complex phase steel material prepared by the present invention is martensite, bainite and a small amount of residual austenite. Figure 1 and Figure 2 As shown. This scheme firstly s-50% The isothermal quenching temperature is calculated, the treatment temperature of each step of the heat treatment is set, and then the metallographic analysis is performed according to the microstructure of the obtained steel material. For example, the proportion of each organization is calculated using a 4XCE inverted metallographic microscope. The results show that the martensite organization in Examples 1-3 is 45-55%, the bainite organization is 40-45%, and the austenite organization is 5-10%; in addition, the product performance of Examples 1-3 is as follows: the organization and performance of the center and surface parts of the product are uniform, the hardness is maintained at 45-50HRC, and the impact toughness is not less than 30J for the U-notch 10*10*55 standard impact specimen; the specific organization proportion and performance test results are shown in Table 3 below.
[0061] Table 3 Product tissue proportion and performance test data of Example 1-3
[0062]
[0063] The steel materials obtained in the above three embodiments and 70Cr 3 NiMo was subjected to abrasive erosion wear tests on a wear testing machine. The medium was quartz sand of 40-70 mesh, the rotation speed was 1425r / min, and the material state was heat-treated. The wear performance comparison data is shown in Table 4 below.
[0064] Table 4 Comparative data on wear properties of cast complex phase steel materials obtained in Examples 1-3
[0065] Serial number Relative wear resistance <![CDATA[70Cr 3 By You]]> 1 Example 1 1.33 Example 2 1.28 Example 3 1.31
[0066] The cast complex steel material suitable for semi-autogenous mill lining plate prepared in Examples 1-3 and 70Cr 3 NiMo conducted a drop ball test and a destructive test on an 8-meter drop ball test machine. The steel ball diameter Material state: heat-treated state, as shown in Table 5 below.
[0067] Table 5 Data analysis of the impact of the number of ball drops on materials in the ball drop test
[0068] Serial number Number of ball drops <![CDATA[70Cr 3 By You]]> 3000 times Example 1 10000 times Example 2 7500 times Example 3 6000 times
[0069] The cast complex steel material suitable for SAG mill lining plate prepared in Example 1 is made into SAG mill lining plate for installation and application. Figure 3 As shown: The specifications of the semi-autogenous mill are The wear rate of the chrome-molybdenum steel liner used by the original manufacturer is 16mm / month, and the wear rate of the cast complex phase steel liner is 12mm / month, and the wear resistance is improved by 33%.
[0070] The cast complex phase steel material prepared by the above method of the present invention can effectively improve the wear resistance and crack resistance of the material. On the one hand, the hardenability of the material is significantly improved by adding Mo, Ni, Cu, and Cr elements to its components. On the other hand, by calculating M s-50% The isothermal quenching process parameters are obtained and the matrix structure is effectively strengthened by isothermal quenching, that is, the martensite structure is introduced and the austenite structure is reduced, so as to ensure the mechanical properties of the steel material; the semi-autogenous mill liner made of the cast complex phase steel material of the present invention has high wear resistance, high yield rate and stable production process, and can completely solve the cracking problem of the semi-autogenous mill liner when used.
[0071] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. A method for preparing a cast complex phase steel material suitable for a semi-autogenous mill liner, characterized in that: The steps include: 1) Smelting in a medium frequency electric furnace to obtain molten iron with the following chemical composition by weight percentage: C is 0.2~0.4wt%, Si is 1.0~1.5wt%, Mn is 1.5~2.5wt%, Cr is 0.5~1.0wt%, Mo is 0.2~0.5wt%, Cu is 0.2~0.5wt%, Ni is 0.2~0.5wt%, Al is 0.02~0.06wt%, P is ≤0.03%, S is ≤0.025%, and the rest is Fe and unavoidable impurities; 2) The smelting temperature rises to 1600℃~1650℃, and the molten iron is poured out of the furnace, and the pouring temperature of the molten iron is controlled at 1500℃~1550℃; 3) A resin sand molding process is adopted, the molding sand is jelly sand, and furan resin and benzenesulfonic acid curing agent are added; wherein the mass ratio of the jelly sand to the sand iron of the casting is 3-5:1, the amount of the furan resin added is 1.1-1.2% of the mass of the jelly sand, and the amount of the benzenesulfonic acid curing agent added is 30-50% of the mass of the furan resin; 4) The castings that have been unpacked, cooled to room temperature, and then cleaned are pretreated in a heat treatment furnace, wherein the pretreatment includes two processes of normalizing and isothermal spheroidizing annealing performed in sequence; wherein the normalizing process is to keep the castings in a furnace at 950-1050°C for 4-8 hours, and then air-cool them to room temperature after being taken out of the furnace; and the isothermal spheroidizing annealing process is to keep the castings in a furnace at 800-900°C for 4-8 hours, and then cool them to 700-750°C for 4-8 hours with the furnace, and then air-cool them to room temperature; 5) The pretreated casting is subjected to isothermal quenching treatment. The isothermal quenching process is as follows: the casting is heated to 900-950°C in a heat treatment furnace and kept at this temperature for 4-8 hours, then quickly transferred to a salt bath for isothermal quenching at 230 Keep at ~250℃ for 4~6h and then take out of the oven; 6) The casting after isothermal quenching treatment is tempered twice to obtain a cast complex phase steel material, wherein the temperature of the first tempering treatment is 300-350°C, the temperature of the second tempering treatment is 200-250°C, and the holding time is 4-8h respectively; The raw materials for obtaining molten iron by smelting in a medium frequency electric furnace in step 1) include scrap steel, carburizer, low carbon ferrochrome, ferromolybdenum, nickel plate, copper plate, ferromanganese, ferrosilicon and aluminum wire added to the medium frequency electric furnace in sequence; the organizational structure of the cast complex phase steel material obtained in step 6) includes 45-55% martensite, 40-45% bainite and 5-10% residual austenite.
2. The method for preparing a cast complex phase steel material suitable for a semi-autogenous mill liner according to claim 1, characterized in that: The hardness of the cast complex phase steel material is 45-50HRC.
3. The method for preparing a cast complex phase steel material suitable for a semi-autogenous mill liner according to claim 1, characterized in that: The U-notch impact toughness of the cast complex phase steel material is not less than 30 J / cm 2 .
4. The method for preparing a cast complex phase steel material suitable for a semi-autogenous mill liner according to claim 1, characterized in that: The chemical components include the following mass percentages: C is 0.3~0.4wt%, Si is 1.3~1.5wt%, Mn is 1.5~2.0wt%, Cr is 0.6~0.9wt%, Mo is 0.3~0.4 wt%, Cu is 0.3~0.4wt%, Ni is 0.4~0.5 wt%, Al is 0.03~0.06wt%, P is ≤0.03%, S is ≤0.025%, and the rest is Fe and unavoidable impurities.
5. The method for preparing a cast complex phase steel material suitable for a semi-autogenous mill liner according to claim 1, characterized in that: When the casting is subjected to pretreatment or isothermal quenching treatment in a heat treatment furnace, when the temperature in the heat treatment furnace is less than 650°C, the temperature is increased at a rate of 100-150°C / h; when the temperature in the heat treatment furnace exceeds 650°C, the temperature is increased at a rate of 150-200°C / h.
6. The method for preparing a cast complex phase steel material suitable for a semi-autogenous mill liner according to claim 1, characterized in that: In step 4), the casting is cooled in the sand box to below 400° C., and then the sand box is opened.
Citation Information
Patent Citations
Alloy steel and preparation technology thereof
CN108315658A
Cast bainite steel for semi-autogenous mill, preparation method of cast bainite steel and semi-autogenous mill cast bainite steel lining plate
CN113235005A
Anti-fracture and anti-fatigue lining plate of semi-autogenous mill and preparation method thereof
CN114622131A